Analysis of Teachers' Difficulties in Instilling the Character of Discipline and Responsibility of Elementary School Students After Covid 19 - Putri Kusuma Wardani; Ratnasari Diah Utami (Elementary Teacher Education Program, Majalengka University, 2024)
Learning is now changing to face-to-face learning after previously being carried out online for more than a year during the COVID-19 pandemic. Direct learning after the pandemic has greatly affected the formation of student character, especially in terms of responsibility and discipline. This descriptive qualitative research aims to explain the difficulties and solutions of teachers in instilling discipline and responsibility values in students at SD Muhammadiyah 3 Surakarta after the COVID-19 pandemic. The resource person was a grade II teacher of SD Muhammadiyah 3 Surakarta. Data collection is done through observation, interviews, and documentation. Data validity tests are performed using data source triangulation techniques and method triangulation. The data analysis techniques used are data reduction, data presentation, and conclusions. The results of the research found by researchers can be concluded that: first, there are difficulty factors that hinder teachers in an effort to instill discipline character education and responsibility in students, including: lack of student learning motiivation, diverse student characters, situations and conditions of the new normal period, student absorption, lack of cooperation between parents and educators. Second, the teacher's solution in instilling the character of discipline and responsibility is by carrying out activities: example, habituation, awareness, supervision and control.Keywords: Difficulty, Character, Discipline, Responsibility